Effect of peripheral canal on growth, survival and production of shrimp (Penaeus monodon) in traditional rice-shrimp culture system in south-west coastal region, Bangladesh - Islam, ML; Moniruzzaman, M; Alam, MJ; Shofiquzzoha, AFM (Journal of the Bangladesh Agricultural University, 2010)
The effect of peripheral canal on growth, survival and production of shrimp (Penaeus monodon) has been assessed. The depth of peripheral canal was varied as 0.7 m (T1) and 0.9 (T2), while the width of canal kept similar (1.5 m) in all the treatments. There was also a set of experimental plots without peripheral canal (T3). Each treatment had two replications. The experiment was designed for a culture period of 120 days with the stocking density of 3PL/m2. Results on growth, survival and production performance revealed no significant difference (p>0.05) among the treatments, but apparently higher body weight gain (23.42±0.735g), survival rate (31.90±14.959%) and production (225.79±112.140kg/ha) were obtained from T2 (peripheral canal of 1.5 m x 0.9 m). In case of survival rate and production, greater deviations were found in all the treatments that indicated differences among the replicated plots in each treatment. The plot under T2 provided highest production of 305.05 kg/ha of shrimp with the highest survival rate of 42.48%. It has been an indication of combined effect of depth and canal on the production. Though direct effect of peripheral canal on production was not observed, but strong correlation between water depth on platform area with production (r=0.935); survival rate (r=0.923) and weight gain (r=0.912) was ascertained. Keywords: Effect; Peripheral canal; Production; Tiger shrimp DOI: 10.3329/jbau.v7i1.4981 J. Bangladesh Agril. Univ. 7(1): 169-174, 2009